Sexual Violence in Ethiopian Higher Education - Woldegiyoirgis, Ayenachew (International Higher Education, 2018)
Several studies have shown the shocking extent of sexual violence in the Ethiopian higher education. Situated in the deep-rooted culture of gender bias, the problem is both at institutional and systemic levels. This article proposes a peer-based alternative that empowers students as bystanders in fighting sexual violence on campus.